The land, the struggle and the implantation of the Agricultural Family School of the Bico do Papagaio Padre Josimo in the State of Tocantins, Brazil (Research, Society and Development, 2020)
This paper analyzes the process of struggle for land and the implementation of the Agricultural Family School of the Bico do Papagaio Padre Josimo (AFSBIP) in Esperantina, state of Tocantins. To this end, we sought to understand how the historical process of struggle for land and agrarian conflicts took place in the micro-region of the Bico do Papagaio, the mobilization of social movements in the struggle for a school for the rural people of the region, to then understand aspects of AFSBIP’s historical trajectory. It is a qualitative research, bibliographic and documentary in nature. The corpus consists of school-camp documents and four interviews with social actors in the community. The investigation revealed that the process of fighting for land in this region was very tense for peasants, with many conflicts and deaths. The results of the research also contribute to making the history of the struggle for land and the creation of this agricultural family school always remembered, in addition to the fact that AFSBIP is contributing significantly to the formation of several peasants.